Information-measuring automated system of radiation-meteorological, fire and video control with autonomous power supply - Novik, Alexander N.; Kuchinsky, Petr V.; Khilko, Gennady I.; Kozhemyakin, Valeriy A.; Bystrov, Evgeny V. (Journal of the Belarusian State University. Physics, 2023)
To automate the process of monitoring the radiation and fire situation of the territory, an automated system of radiation-meteorological, fire and video control with autonomous power supply was developed and put into trial operation. The system consists of two independent and mutually complementary subsystems (the radiation-meteorological control subsystem and the fire and video control subsystem) and is a hierarchical information network with territorially separated radiation-meteorological and video control posts based on 31 fire observation towers. All posts include software and hardware that ensure the functioning of the system according to specified algorithms for collecting, processing, storing and displaying information. In addition, each post maintains communication links to ensure the delivery of information within the information network. The system includes a response centre, which is equipped with software and hardware for receiving, processing, storing and displaying information from radiation-meteorological and video control posts. Communication between the radiation-meteorological and video control posts and the response center is carried out via the Internet. This configuration of the system provides territorial flexibility in choosing the location of the response centre and easy integration of different levels of the system with each other. A feature of the system is the equipping of stations with no industrial supply network with photovoltaic power plants. The purpose of the system is reliable, credible, continuous automated monitoring of the radiation and fire situation for early detection of fires and prompt decision-making in the event of natural and man-made emergencies.